WEBSITE DESIGN AS A PROMOTIONAL MEDIA SWIMMING POOL LENTANA GARDEN IN GISTING - Roji, Fahrul; Kasmi, Kasmi; Nurparijah, Nurparijah (JMBI (Journal of Marketing and Business Intelligence), 2023)
Along with current technological developments, technology is the development of digital technology has significantly influenced business promotion strategies, including in the tourism and hospitality sectors. This study focuses on website design as a promotional media for Swimming Pool Lentana Garden in Gisting. The purpose of this research is to design an effective and informative website that enhances visitor engagement and increases brand awareness. The research utilizes a qualitative approach, involving data collection through observations, interviews, and literature studies. The website is designed with a user-friendly interface, attractive visuals, and essential features such as location details, pricing, facilities, and online booking options. The results indicate that a well-structured website can serve as an effective marketing tool, reaching a wider audience and improving customer experience. In conclusion, website design plays a crucial role in strengthening promotional efforts and boosting visitor interest. Future improvements may include integrating social media, search engine optimization (SEO), and customer review features to enhance website performance and visibility.